Pengaruh POC Kombinasi Ampas Teh dan Sabut Kelapa terhadap Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens) - Firdanatul Istiqomah; Suparti Suparti (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Cayenne pepper is one of the most popular horticultural crops, therefore fertilization can be used to increase the growth of chili plants. This research was conducted to determine the effect of the POC combination of tea dregs and coconut coir on the growth of cayenne pepper. The study was conducted using an experimental method using a completely randomized design (CRD) factorial pattern, namely POC concentration factor P0 (without giving POC), P1 (100 ml POC tea dregs and coconut coir + 900 ml water), P2 (200 POC tea dregs and coconut coir ml + 800 ml water), P3 (POC tea dregs and coconut coir 300 ml + 700 ml water) and time intervals H1 (3 days), H2 (6 days). Observational data were analyzed by ANOVA test with 5% confidence level. The parameters measured were plant height, number of leaves and wet weight. The best growth of cayenne pepper plants was in the P3H2 treatment (300 ml POC concentration + 700 ml water and 6 days interval) with an average plant height of 24.5 cm, 8 leaves and 14.5 g fresh weight.